2001
DOI: 10.1103/physrevlett.86.3435
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Driven DNA Translocations through a Nanopore

Abstract: The Harvard community has made this article openly available. Please share how this access benefits you. Your story matters. Voltage-Driven DNA Translocations through a Nanopore We measure current blockade and time distributions for single-stranded DNA polymers during voltagedriven translocations through a single a-hemolysin pore. We use these data to determine the velocity of the polymers in the pore. Our measurements imply that, while polymers longer than the pore are translocated at a constant speed, the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

60
967
14
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 860 publications
(1,042 citation statements)
references
References 14 publications
60
967
14
1
Order By: Relevance
“…They also found that the rate of entry is higher when the DNA enters the channel through the protein's larger vestibule rather than through the other end. Meller and co-workers [7] also studied this particular system in the presence of a voltage difference along the channel. They found that the translocation speed of long ssDNA strands, i.e., longer than the channel, is independent of the polymer length.…”
Section: Nanopore Technologiesmentioning
confidence: 99%
“…They also found that the rate of entry is higher when the DNA enters the channel through the protein's larger vestibule rather than through the other end. Meller and co-workers [7] also studied this particular system in the presence of a voltage difference along the channel. They found that the translocation speed of long ssDNA strands, i.e., longer than the channel, is independent of the polymer length.…”
Section: Nanopore Technologiesmentioning
confidence: 99%
“…Detailed insight has been gained from studies on pores of known molecular structure and the electrophoretically-driven movement of individual DNA and RNA strands. 3,11,21,23,[28][29][30] Several biophysical parameters have been determined such as threading frequency, [31][32][33][34] orientation of strands, [35][36][37][38][39] velocity of DNA transport, 40 influence of pore geometry, 41 and interactions with the pore wall. 39 In addition to nucleic acids, translocation has also been investigated for peptides, [42][43][44][45] proteins, [46][47][48] and peptide-oligonucleotide conjugates, 49 which, unlike nucleic acid strands, frequently feature inhomogeneous charge distributions and vary considerably in diameter along the polymer sequence.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2] Subsequently, the pioneering studies of the use of R-hemolysin protein pore within a lipid bilayer for the translocation of single strands of DNA molecules using a voltage bias across the membranes sparked tremendous interest in such single molecule sensors. [3][4][5][6][7][8] The normal ionic current through the protein pore in a lipid bilayer would detectably reduce as a polyanionic chain of ssDNA molecules traversed through the pore, even allowing the distinction between polycytosine and polyadenine molecules, thus demonstrating the potential of single base discrimination in these sensors. 4,5 Despite these advantages, robust integration of these biological sensors within practical devices is quite problematic, and a mechanical pore 9,10 provides numerous advantages over biological pores.…”
mentioning
confidence: 99%
“…Recent reports of the use of ion milling 7 and transmission electron beam imaging 15,16 with real time feedback to form controlled pore size have paved the way to begin the exploration of single DNA molecule translocations and conformational studies using artificial pores. The electronic signature of dsDNA moving through these nanopores can be quite complex and the conformational changes in the molecule cannot be ignored, as shown recently by Li et al 9 One possibility to suppress signatures due to conformational changes is to increase the entropic energy barrier for molecules to enter the nanopore by the use of "channels" with nanoscale diameters.…”
mentioning
confidence: 99%